A 90-Day Oral Toxicity of Hydroethanolic Root Extract of Carissa spinarum in Wistar Rats. (20th April 2021) - Dossou-Yovo, Komlan M.; Diallo, Aboudoulatif; Lawson-Evi, Povi; Kantati, Yendubé T.; Darré, Tchin; Bakoma, Batomayena; Eklu-Gadégbéku, Kwashie
Abstract : Background . Herbal medication is a worldwide and ancient practice, mostly in developing countries, where a large part of the population is involved in this practice. Hence, studies must be conducted to evaluate their safety and efficiency to avoid or prevent toxicological risks due to their usage. In Togo, Carissa spinarum is a medicinal plant belonging to Apocynaceae family, used as an aphrodisiac or to heal some ailments including malaria, sickle cell anemia, hypertension, pain, and asthma. Notwithstanding its several ethnomedicinal benefits, just a few toxicological data associated with its chronic use are available. Objective . Therefore, this study aims to assess the toxicity of an ethanolic root extract of Carissa spinarum in Wistar rats. Methods . The 90-day oral toxicity process following OECD TG 408 guidelines is used. Male Wistar rats received Carissa spinarum root hydroethanolic extract at 500 and 1000 mg/kg for 90 days by oral gavage. Body weight changes, hematological and blood biochemical parameters, organ weight changes, malondialdehyde as a lipoperoxidation marker expressed according to tissue proteins, and histopathology of vital organs were assessed. Results . No signs of toxicity or mortality were observed during the 90 days experiment. Hematological parameters have not shown any treatment-related abnormalities. According to biochemical parameters, an increase in the chloride ion level was observed at 1000 mg/kg p < 0.01 . There was no significant difference between the treated groups and the control group concerning the malondialdehyde concentration, body weight, and organ relative weight. No changes in necropsy and histopathology of vital organs associated with extract treatment were observed. Conclusion . The results indicated that an ethanolic root extract of Carissa spinarum does not cause adverse effects, which can lead to Wistar rats' death after 90-day oral administration at 500 and 1000 mg.